Human colonic fibroblasts regulate stemness and chemotherapy resistance of colon cancer stem cells. Issue 12 (17th June 2016) - Colak, S.; Medema, J.P.
Abstract: There is increasing evidence that cancers are heterogeneous and contain a hierarchical organization consisting of cancer stem cells and their differentiated cell progeny. These cancer stem cells are at the core of the tumor as they represent the clonogenic cells within a tumor. Moreover, these cells are considered to contain selective therapy resistance, which suggests a pivotal role in therapy resistance and tumor relapse. Here we show that differentiated cells can re-acquire stemness through factors secreted from fibroblasts. This induced CSC state also coincides with re-acquisition of resistance to chemotherapy. Resistance induced in newly formed CSCs is mediated by the anti-apoptotic molecule BCLXL and inhibition of BCLXL with the BH3 mimetic ABT-737 sensitizes these cancer cells toward chemotherapy. These data point to an important interplay between tumor cells and their microenvironment in the regulation of stemness and therapy resistance.